Recurrence and outcomes of Stevens-Johnson syndrome and toxic epidermal necrolysis in children - Finkelstein, Yaron (2011)
OBJECTIVES: To report clinical course, etiology, management, and long-term outcomes of children suffering from Stevens-Johnson syndrome (SJS) or toxic epidermal necrolysis (TEN). METHODS: We conducted a study of all pediatric patients with SJS or TEN admitted between 2000 and 2007 to the Hospital for Sick Children and Children's Hospital Boston, and particular attention was paid to clinical manifestations, etiology, mortality, and long-term outcomes. RESULTS: We identified 55 cases of SJS (n = 47), TEN (n = 5), or SJS/TEN overlap syndrome (n - 3). Drugs were identified as the most likely etiologic agent in 29 children (53%); antiepileptic drugs were the most common agents (n = 16), followed by sulfonamide antibiotics (n = 7) and chemotherapy drugs (n = 2). Acute Mycoplasma pneumoniae infection was confirmed in 12 children (22%), and herpes simplex virus was confirmed in 5 children (9%). Treatment regimens differed significantly between participating sites and included systemic antimicrobial agents (67%), systemic corticosteroids (40%), and antiviral drugs (31%). Intravenous immunoglobulin was administered to 21 children (38%), of whom 8 received concomitant systemic corticosteroids. Ten children (18%) had recurrence of SJS up to 7 years after the index episode, and 3 experienced multiple recurrences. Twenty-six children (47%) suffered long-term sequelae that mostly involved the skin and eyes. CONCLUSIONS: Mortality rate in children was lower than that reported in adults, but half of affected children suffered long-term complications. The recurrence rate of SJS was high (1 in 5), which suggests vulnerability and potential genetic predisposition. In the absence of standardized management guidelines for these conditions, treatment regimens differed significantly between participating institutions.